ANALISIS POTENSI PENERIMAAN PAJAK HOTEL DI KOTA TOMOHON - Rawung, Megha Cicilia; Karamoy, Herman; Elim, Inggriani (ACCOUNTABILITY, 2015)
Regional Income is a source of regional finance and government financing. One of the original income receipts derived from the Regional Tax one of which is tax Hotel. This study was conducted to determine the potential of the hotel tax, the level of effectiveness and Contributions Taxes as a source of regional revenue Tomohon. The analysis method used is descriptive method Quantitative and analyze tax receipts Hotel of the Year 2011-2014. The results showed that the level of effectiveness of a Hotel Tax Year 2011-2014 ineffective. Taxes contribution as a source of regional revenue Tomohon over the last four years and a maximum rated not included in the criteria for contributions "very poor". Based on the results of tests conducted by researchers Potential Pick Taxes owned by the City of Tomohon is Rp.333.140.460. The existence of several barriers such as the lack of supporting facilities such as places of entertainment, which is not accurate setting of targets as well as the threat of natural disasters makes visitors reluctant to stay in Tomohon. Extension of paying taxes to the public awareness and create art festival activities are some of the efforts that have been made by the government to increase the contribution of hotel tax as a source of regional revenue in Tomohon.